The foundations of Islamic banking : theory, practice and education - Mohamed Ariff, 1942-; Iqbal, Munawar (Cheltenham Northampton, MA ; Edward Elgar, 2011)
Examines the roots of the principles of ethical Islamic financial transactions, which have evolved over several millennia, on issues including usury, interest rates, and financial contracting for funding enterprises, mortgages, leasing and other transactions. Regulatory and governance issues are discussed, and the practice and operation of Islamic financial institutions are explained via three distinct case studies. The final chapter looks at what steps are being taken to provide professional accreditation to Islamic banking professional personnel and prescribes requirements for training in this growing industry. From publisher description.
Includes bibliographical references and index.
oif 22/05/14
Loan
Keywords: Banks and banking -- Religious aspects -- Islam..; Banks and banking -- Islamic countries; Finance -- Islamic countries; Banking law (Islamic law); Finance -- Religious aspects -- Islam